Antioxidants profile of Momordica charantia fruit extract analyzed using LC-MS-QTOF-based metabolomics - Perumal, Vikneswari; Khatib, Alfi; Ahmed, Qamar Uddin; Uzir, Bisha Fathamah; Abas, Faridah; Murugesu, Suganya; Saiman, Mohd Zuwairi; Primaharinastiti, Riesta; El-Seedi, Hesham (Elsevier, 2021)
Momordica charantia fruit is claimed to have healthy benefit. Despite this potential claim, the phytochemical study of this fruit is still lacking. Thus, this study aimed to evaluate the antioxidants profile of Momordica charantia (Cucurbitaceae) fruit. The antioxidant activity of the ethanolic extracts of various polarities was evaluated and the metabolites that are responsible for its activity were identified using metabolomics approach. Six different mixture of ethanol in water that are 0%, 20%, 40%, 60%, 80%, and 100% (v/v) was extracted using dveseeded fruit sample. Liquid chromatography-mass spectrometry-quadrupole time of flight and multivariate data analysis was used to identify the metabolites that were either antioxidants or pro-oxidants. The 80% ethanol extract exhibited the most antioxidant activity when tested in both 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) antioxidant assays. This extract showed the most intense LC-MS signals represented to ascorbic acid, margarolic acid, brevifolincarboxylic acid, quercetin 3-O-glycoside, kuguacin H, cucurbitacin E, 3-malonylmomordicin I, and goyaglycoside G correlating to the anti-oxidant activity. This study reports for the first time the existence of brevifolincarboxylic acid in this fruit, and the antioxidant activity of 3-malonylmomordicin I and goyaglycoside G. In addition, the loading plots revealed the unknown compounds possessing the antioxidant activity which are potential to be isolated in the future study.